ФЕМИНИЗМ В. ВУЛЬФ В ЕЁ ТВОРЧЕСТВЕ - Мусаева, А. Г. (Eurasian Journal of Philology Science and Education, 2015)
This article is written about 2 different tendentious in the world literature which outlined at the end of XIX the beginning of XX centuries. Some of the writers tried to explore the inner world of each person, the others tried to seize the huge spacecountries, continents. The first writers studied extensive problems of human, the seconds studied the intensive feelings in humans mind. One of the writers who explored the inner world of human mind was Virginia Wolf. She didn’t live very long, but her creation was multisided very much. In this context writer took up the problem of woman’s fate. Each of her works imbues with herself and through her own experience she tried to bare woman’s spirit. Brilliant example of this is the novel “At the Lighthouse”.